Assessment of subsidence in Delhi NCR due to groundwater depletion using TerraSAR-X and persistent scatterers interferometry. (2nd January 2019) - Malik, Kapil; Kumar, Dheeraj; Perissin, Daniele
ABSTRACT: Currently, high-resolution SAR data is available from different satellites. These datasets have been proved to be a strong source to monitor land subsidence. This paper aims to use high-resolution Persistent Scatterers Interferometry (PSI) to estimate the urban subsidence in Delhi NCR. TerraSAR-X images in 68 numbers spread over a period of 26 months during September 2011 – September 2013 have been used to assess the land surface subsidence. The study area is covered with large infrastructure projects such as railway lines, bridges, highways, metro bridges and tunnels. The resultant surface subsidence has been compared with the groundwater table data and it appears that most of the subsidence has been induced by the over-exploitation of groundwater in the area. In some areas, we can clearly see that the rapid construction activities contributing to the surface subsidence phenomenon. Development of a new construction project required groundwater to be used in the activity which impacts the groundwater table. This deterioration of the groundwater table has led to the land subsidence. The study suggests that there is an urgent need to address the issue of groundwater exploitation in the affected areas to check the current phenomenon of subsidence. This is a distinctive work carried out over the study area.